The Influence of Combined Turbulators on the Hydraulic-Thermal Performance and Exergy Efficiency of MWCNT-Cu/Water Nanofluid in a Parabolic Solar Collector: A Numerical Approach - Khetib, Yacine; Melaibari, Ammar; Alsulami, Radi (Frontiers in Energy Research, 2021)
The present research benefits from finite volume method to investigate the influence of combined tabulator on the thermal and hydraulic exergy of a parabolic solar collector which hybrid 2-phase MWCNT-Cu/water nanofluid passed in. All the parabolic geometries are produced in design modeler software. Furthermore, FLUENT software that is equipped with SIMPLE algorithm is applied for the analysis of the performance of thermal and hydraulic, and exergy efficiency. The eulerian-eulerian multiphase model and k-ω were opted for simulating 2-phase the hybrid MWCNT-Cu/water nanofluid and turbulence model in the collector. The research was analyzed in torsion ratios from 1 to 4, Re numbers from 6000 to 18000 (turbulent flow), and the volume fraction of nanofluid to 3%. The numerical outcomes confirm that the most heat transfer and lowest pressure drop is relevant to Re number of 18000, the nanofluid volume fraction of 3%, and torsion ratio of 4. Furthermore, in all torsion ratios, rising Re number and volume fraction lead to more exergy efficiency. The maximum value of 26.32% in the exergy efficiency was obtained at a volume fraction of 3%, Torsion ratio of 3, as the Re number goes from 60000 to 18000.